Modeling of cool roof heat transfer in tropical climate. (March 2015) - Zingre, Kishor T.; Wan, Man Pun; Tong, Shanshan; Li, Hua; Chang, Victor W.-C.; Wong, Swee Khian; Thian Toh, Winston Boo; Leng Lee, Irene Yen
Abstract: Cool roof is gaining popularity as a passive building energy saving solution. A concise and easy-to-apply mathematical model is essential for building designers to evaluate the impact of cool coating on heat transfer and indoor thermal comfort. A novel cool roof heat transfer (CRHT) model was developed using the spectral approximation method. The CRHT model was verified against the conduction transfer function method and was validated against experiments performed in two identically configured apartments with concrete roofs in Singapore. The model predictions show that on a sunny day, a cool coating (solar reflectance of 0.74) reduces the peak roof temperature, indoor air temperature and daily heat gain by up to 14.1 °C, 2.4 °C and 0.66 kWh/m 2 (or 54%), respectively through the concrete roof. The model predictions match with experimental measurements with reasonable accuracy. Further model predictions suggested that significant daily heat gain reduction can also be achieved by cool coating on galvanized steel (metal) roofs. The daily heat gain reduction brought by the cool coating drops as the roof exposes to higher wind speeds. The proposed CRHT model largely simplifies the calculation of heat transfer of cool roofs, compared to existing methods, and is generally applicable to opaque solid surfaces (roofs and walls). Highlights: A novel cool roof heat transfer (CRHT) model is proposed using spectral approximation method. The CRHT model is concise and applicable to naturally ventilated (NV) buildings. The CRHT model is applicable to all opaque building surfaces (walls and roofs). The CRHT model is verified against CTF method and validated against experiments. Impact of cool coating is studied for concrete and metal roofs of NV buildings.